Comparing customer perceptions of hotel and peer-to-peer accommodation advantages and disadvantages. Issue 2 (12th February 2018) - Birinci, Hasan; Berezina, Katerina; Cobanoglu, Cihan
Abstract : Purpose: The purpose of this paper is to compare customer perceptions of hotel and peer-to-peer (e.g. Airbnb) accommodation advantages and disadvantages and examine their influence on customer satisfaction and repurchase intentions. The advantages of each accommodation type are conceptualized through perceived travel experience authenticity, whereas the disadvantages are evaluated through the risks associated with staying at each accommodation type, including product performance risk, time/convenience risk and safety and security risk. Design/methodology/approach: A cross-sectional survey was designed and disseminated to gather the data necessary to fulfill the study objectives. A total of 391 usable responses were collected for a multi-group analysis of the structural model designed to test the proposed relationships. Findings: The multi-group comparison revealed similarities between the peer-to-peer (Airbnb) and hotel guest structural models. Model testing revealed a strong positive relationship between satisfaction and repurchase intention. Perceived authenticity was identified as a statistically significant satisfaction predictor for both accommodation types. Time/convenience and product performance risks were found to be insignificant predictors of guest satisfaction, while safety and security risk appeared to be statistically significant only in the Airbnb sample. Research limitations/implications: This study's recruited sample represented a higher concentration of younger travelers, and, therefore, might only be generalized to the corresponding US traveler group population. Additionally, samples recruited via Amazon's MTurk may be subject to self-selection bias as any other non-probability samples. Consequently, further research with a larger and more diverse sample is recommended. Practical implications: It is recommended for both hotels and Airbnb to strengthen the authenticity of their accommodation offerings to provide a better guest experience and increase consumer satisfaction. Social implications: To develop the authenticity component, Airbnb hosts and hotels may offer local experiences to their customers, where guests would be able to engage with the community and to see and feel how the city lives. Such partnerships may not only improve the traveler experiences but also support the local community and strengthen the ties between local businesses. Originality/value: This study contributes to the literature by advancing understanding of peer-to-peer (Airbnb) versus hotel accommodation consumer preferences. This study offers relevant theoretical constructs for assessing both accommodation types' advantages and disadvantages.